A STUDY ON CENTRE GOODS AND SERVICE TAX- STATE GOODS SERVICE TEX (CGST-SGST) IN INDIA AN OVERVIEW (International Journal of Food and Nutritional Sciences, 2022)
The Present study conducted the Goods and Service Tax- State Goods Service Tex (CGST-SGST) in India an Overview. GST is a comprehensive indirect tax levy on manufacture, sale and consumption of goods as well as services at the national level. It will replace all indirect taxes levied on goods and services by states and central. Under the pre GST taxation system for indirect taxes number of indirect taxes were being levied and collected at multiple rates both by central government and state governments on different activities undertaken